Resistencia bacteriana en bacilos Gram negativos de cultivos aislados de muestras clínicas en pacientes hospitalizados del hospital “Manuel Ygnacio Monteros” durante el periodo octubre-noviembre 2013 - Chalán Cabrera, Lucía Alexandra (2014)
The objective of this assay was to identify and determinate the bacterial resistance mechanism in gram negative bacilli from isolated cultures of clinic samples of inpatients of “Manuel Ygnacio Monteros” Hospital during the October – November 2013 period. To identify these strains, it was performed biochemical tests and bacterial susceptibility was determined by disk diffusion method (Bauer and Kirby technique); considering the bacterial resistance to 3G cephalosporin, cefoxitin and carbapenems, it was performed confirmatory tests following the recommendations of the CLSI 2012; the susceptibility profile of the isolated strains were analyzed using the WHONET program. It was collected 88 cultures, being the urine sample the most common, 43,2%, the most frequently isolated strain was Escherichia coli, 60,6% in inpatients and 31,8% in ICU. It was identified 45 beta-lactamases producers strains distributed as the following way; BLEE producer strains: 86,7% in hospitalization and 13,3% in ICU; AmpC producers strains: 66,7% in hospitalization and 33,3% in ICU; carbapenemase producers strains it was not identified. The results show that in a inpatients of this Hospital there are a high frequency of BLEE.